Chemical Looping of Manganese to Synthesize Ammonia at Atmospheric Pressure: Sodium as Promoter. Issue 10 (2nd September 2020) - Aframehr, Wrya Mohammadi; Huang, Chaoran; Pfromm, Peter H.
Abstract: Affordable synthetic ammonia (NH3 ) enables the production of nearly half of the food we eat and is emerging as a renewable energy carrier. Sodium‐promoted chemical looping NH3 synthesis at atmospheric pressure using manganese (Mn) is here demonstrated. The looping process may be advantageous when inexpensive renewable hydrogen from electrolysis is available. Avoiding the high pressure of the Haber‐Bosch process by chemical looping using earth‐abundant materials may reduce capital cost, facilitate intermittent operation, and allow operation in geographic areas where infrastructure is less sophisticated. At this early stage, the data suggest that 0.28 m 3 of a 50 % porosity solid Mn bed may suffice to produce 100 kg NH3 per day by chemical looping, with abundant opportunities for improvement. Abstract : The addition of NaOH as alkali‐containing promoter significantly improves yield and kinetics of chemical looping of Mn for NH3 synthesis at atmospheric pressure, thus boosting the ammonia harvesting. Based on the feasible reactions on the Mn surface, Na may increase the N conversion to NH3 instead of N2 whereas the reproducibility of successive reproducible looping implies unflinching.